Mechanically Milled Fe-Si-Zn Alloys as Negative Electrodes for Li-Ion Batteries. Issue 12 (12th September 2015) - MacEachern, L.; Dunlap, R. A.; Obrovac, M. N.
Abstract : Fe-Si-Zn alloys prepared by ball milling were investigated as negative electrodes for Li-ion batteries. X-ray diffraction and room temperature 57 Fe Mössbauer measurements were used to characterize alloy structure. Electrochemistry of the alloys was determined at 30°C. Formation of crystalline Li15 Si4 was suppressed during cycling for compositions with greater than 10 at. % Fe. Unlike sputtered films of the same composition, the incorporation of Zn in these ball milled alloys did not suppress Li15 Si4 formation. Instead, Zn behaved as if it were in a physical mixture with the other alloy components. This study shows that sputtered and ball milled alloys of the same composition can have very different electrochemical properties.